Exploitation rates and oceanographic characteristics of anchovy fishing grounds in FMA-572 West Sumatra - Farhan Ramdhani; Septy Heltria; Ester Restiana Endang Gelis; Rizky Janatul Magwa; Noferdiman Noferdiman; Muhamad Gilang Arindra Putra; Muhammad Halim (Depik, 2024)
Anchovy is one of potential commodities widely found and caught by fishermen in FMA-572 West Sumatra. Examining its exploitation rate is a part of taking control and monitor toward the fishing activities to avoid overfishing possibility. This recent study aims to calculate exploitation rate and oceanographic characteristics of anchovy fishing grounds. The data was collected from Bungus Oceanic Fishing Port, West Sumatra in 2018-2022. Meanwhile, sea surface temperature and chlorophyll data were obtained from https://marine.copernicus.eu/ and https://oceancolor.gsfc.nasa.gov 2018-2022, respectively. The results showed that the exploitation rate of anchovies in 2020 and 2022 has exceeded maximum sustainable yield categorized as overexploitation with a percentage of 130.44% and 112.84%. Anchovy catches are significantly influenced by oceanographic factors with F value 0.00000115 ( 0.05). An increase in CPUE value is align with chlorophyll increase and in contrary to sea surface temperature. The findings are expected to give an overview related to anchovy fishing activities implementation and become an input for fisheries governance that lead to sustainable fisheries management.Keywords:FMA-572MSYOverfishingSustainable fisheriesStolephorus sp